Enhancing the production through SMED methodology - Kumaravel, D; Sathya Bharathi, R; Kavinandini, M (International Journal of Engineering and Technology, 2018)
Aim of this experiment is to improve the production rate in steering pump manufacturing industry using single minute exchange of die method. Hydraulic steering pump manufacturer oftenface the problem of periodically changing the machine configuration which led to frequent delays. It was observed that most machines need the fixtures to be redesigned. Thus, comes to play the concept of single minute exchangeof Dies. It refers to single-digit time limit wherein every aspect of a setup change is completed in less than ten minutes. SMED is a changeover technique which is implementing to increase the output and decrease the quality losses due to changeovers. By examine the changeover process along with a stronger sense of teamwork and ownership leads to significant reduction in setup and change over times. Purpose of SMED is to find the workactually done and proper utilization of time during the changeover activity. Through the analysis, a better understanding was gained on how to do certain activities, when the line is running and also to determine the task that needs to be done to reduce the fine-tuning activities after the actual changeover. The faster the changeover time, the lesser is downtime of the machine. This project was focused on reducing the setup time based on the ideas of SMED.